Impact of “dry sowing and wet emergence” water regulation on cotton soil water and salt dynamics, root growth and yield - Hu, Qiang; Xiao, Yu; Li, Huqiang; Wang, Xiaofeng; Lin, Jiao; Zhao, Wenqing; Zhou, Zhiguo; Chen, Guodong; Han, Lu; Cao, Nan; Wan, Sumei (Frontiers in Plant Science, 2025)
BackgroundXinjiang, with unique favorable conditions for cotton growth, faces challenges like water scarcity and soil salinization. The dry sowing and wet emergence (DSWE) water regulation technology may alleviate regional water shortages, but its impacts on soil water-salt dynamics, soil desalination rate (SDR), cotton root growth, yield, and irrigation water production efficiency (IWPE) in saline-alkali land remain poorly documented.MethodsA two-year field trial was conducted during 2023 and 2024, involving three different seedling irrigation amounts (W1, 22.5 mm, W2, 37.5 mm, and W3, 45.0 mm) and two drip irrigation frequencies (F1: one-time irrigation and F2: two-time irrigation), resulting in a total of six irrigation combinations, and a local spring irrigation amount was conducted as CK.ResultsResults demonstrated that under the same emergence water amount, F2 treatment exhibited higher soil moisture content and lower soil salt content compared to F1. Increased irrigation frequency and enhanced emergence water amount (W2F2 and W3F2) had greater root length density (RLD) and root vitality, but a lower root-shoot ratio. The W2F1 and W3F1 treatments significantly increased the activities of peroxidase (POD), superoxide dismutase (SOD), and the content of malondialdehyde (MDA) in cotton roots. In contrast, the activities of POD, SOD, and catalase (CAT), as well as the MDA content in cotton roots under the W2F2 and W3F2 treatments were comparable to those in the CK, indicating no obvious physiological stress. Compared with F1, F2 significantly increased cotton boll number and seedcotton yield by 23.3% and 23.5%, respectively. Notably, however, there were no significant differences in boll number and seedcotton yield among the CK, W2F2, and W3F2 treatments, suggesting that increasing water amount did not further improve yield.ConclusionIn conclusion, DSWE technology maintains optimal soil moisture levels, thereby improving root system development, while simultaneously leaching salts from the rhizosphere and reducing oxidative stress. Under the current experimental conditions, the W2F2 treatment emerges as the most effective strategy for regulating seedling emergence water, effectively integrating water conservation, salinity reduction, and seedling vigor enhancement.